Oil and Macroeconomic (In)Stability - Hilde C. Bjørnland; Vegard Høghaug Larsen; Junior Maih (Norges Bank, 2016)
We analyze the role of oil price volatility in reducing U.S. macroeconomic instability. Using a Markov Switching Rational Expectation New-Keynesian model we revisit the timing of the Great Moderation and the sources of changes in the volatility of macroeconomic variables. We find that smaller or fewer oil price shocks did not play a major role in explaining the Great Moderation. Instead oil price shocks are recurrent sources of economic fluctuations. The most important factor reducing overall variability is a decline in the volatility of structural macroeconomic shocks. A change to a more responsive (hawkish) monetary policy regime also played a role.
hdl:11250/2495717
Keywords: C11; E32; E42; Q43; 330